FPGA Realization of PID Controller Based on BP Neural Network - Shanyong Xu; Yourui Huang; Liguo Qu; Chaoli Tang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Through coordinately work of input layer module, hidden layer module, output layer module and back propagation calculation module to complete the whole system of the closed-loop calculation, this is a process of FPGA realization of PID controller based on BP neural network. Operation of the entire system with FPGA internal clock coordination is unified coordination, just provide clock and reset signals can automatically tune parameters of PID controller. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3464